Utilization Of Pawned Land In Martadah Village Community Based On The Perspective Of Shafi'i Madzhab - Khairiyah; Dika Idha Saputri; Nuril Madinah; Abdul Hafiz Sairazi; Ruslan (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract This research is motivated by the problems that occur in Pasar Arba, Sungai Pandan District, where the implementation of the Regional Regulation of Hulu Sungai Utara Regency No. 9 of 2018 concerning Public Order and Community Peace has not been fully implemented optimally. In its implementation, there are still violations by street vendors which result in disruption of road activities and the function of the road shoulder for pedestrians. The purpose of this study is to determine the extent to which the implementation of the North Hulu River Regency Regional Regulation No. 9 of 2018 concerning Public Order and Community Peace in Arba Market, Sungai Pandan District. This research is a field research with a qualitative approach and the research method uses the case study method. Data collection techniques are interviews and documentation. Data processing techniques through editing, classification and interpretation. Data analysis using descriptive qualitative analysis. Based on the results of the research, the Implementation of Hulu Sungai Utara Regional Regulation No.9 of 2018 concerning Public Order and Community Peace towards controlling street vendors in Arba Market, Sungai Pandan District has not been able to be implemented optimally, because on the one hand there are more and more street vendors and on the other hand the limited location to accommodate traders cannot be developed anymore. This can be seen from along the road to Arba Market in Sungai Pandan Subdistrict, which is increasingly filled with street vendors. The inhibiting factors from law enforcers, street vendors or the community itself so that the implementation is not carried out optimally. Abstrak Penelitian ini dilatarbelakangi dengan permasalahan yang terjadi di Pasar Arba Kecamatan Sungai Pandan yang mana pelaksanaan dari Peraturan Daerah Kabupaten Hulu Sungai Utara No. 9 Tahun 2018 Tentang Ketertiban Umum dan Ketentraman Masyarakat belum sepenuhnya dapat dilaksanakan secara maksimal. Dalam pengemplementasiannya masih terdapat pelanggaran-pelanggaran oleh pedagang kaki lima yang mengakibatkan terganggunya aktivitas jalan dan beralih fungsinya bahu jalan untuk pejalan kaki. Tujuan dalam penelitian ini adalah untuk mengetahui sejauh mana penerapan Peraturan Daerah Kabupaten Hulu Sungai Utara No. 9 Tahun 2018 Tentang Ketertiban Umum dan Ketentraman Masyarakat di Pasar Arba Kecamatan Sungai Pandan. Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif dan metode penelitian menggunakan metode studi kasus. Teknik pengumpulan data yaitu wawancara dan dokumentasi. Teknik pengolahan data melalui editing, klasifikasi dan interpretasi. Analisis data menggunakan analisis kualitatif deskriptif. Berdasarkan hasil penelitian, Implementasi Peraturan Daerah Hulu Sungai Utara No.9 Tahun 2018 Tentang Ketertiban Umum dan Ketentraman Masyarakat terhadap penertiban pedagang kaki lima di Pasar Arba Kecamatan Sungai Pandan belum dapat terlaksana secara maksimal, karena disatu sisi pedagang kaki lima yang semakin banyak dan disisi lain keterbatasan lokasi untuk menampung pedagang tidak bisa dikembangkan lagi. Hal ini dapat dilihat dari sepanjang jalan menuju Pasar Arba di Kecamatan Sungai Pandan semakin dipenuhi oleh pedagang kaki lima. Faktor penghambat dari penegak hukum, pedagang kaki lima ataupun masyarakat itu sendiri sehingga penerapannya tidak terlaksana dengan optimal. Keywords: Implementasi, Penertiban, Pedagang Kaki Lima.